apparatus and method to remotely control fluid flow in tubular strings and wellbore annulus - Tahoun, Ahmed; Kafafy, Raed; Jawamir, Karam; Mohammed Aldheeb, Mohammed Abdulmalek; Khalil, Abdul Mushawwir (2016)
A method and apparatus for remotely and selectively controlling and altering fluid flow through tubular string disposed within a wellbore and further control fluid flow between the tubular string inner flow passage and the annular flow passage, and a method for selectively and remotely receiving and interpreting a form of command or information at a particular apparatus within the wellbore caused by the operator on earth surface through a change of a physical property of the environment. The apparatus comprising a body, a valve operable in plurality of states, an actuator, and an activator responsive to a change of a physical property of the environment caused by the operator on earth surface